Prediction of the Radiative Properties of Triangular-Grating Surfaces from Electromagnetic Theory - Taoufik Ghabara (Journal of Engineering)
In this paper, we present a study of the influence of roughness on the bidirectional reflectivity and on the emissivity of surfaces using Maxwell’s electromagnetic theory. In this framework, we solve the Helmholtz equations by using the surface integral method. We first proceed to a general description of this method, allowing to solve the propagation equations of the electromagnetic field. We then express the diffused directional flux using the surface field and its normal derivative (source terms), in the case of an incident plane wave in “p” polarization or in “s” polarization. This finally allows us to arrive at the desired radiative properties. We have developed two numerical calculation codes whose use we limit to cases of surfaces presenting cavities in the shape of a symmetrical or asymmetrical “V”. Particular interest was given to the influence of the geometric parameters of these surfaces on the bidirectional reflection function and on the emissivity of these surfaces. Finally, we present some very conclusive results.